Factors Affecting the Revenue of Furniture Companies in Majalengka - Dede Komariah; Syaeful Bakhri; Layaman Layaman (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
The furniture industry in Cigasong District, Majalengka Regency, is a pivotal force in the local economy. However, sustained growth and prosperity for bothowners and employees rely heavily on consistent business income. This study, therefore, investigates the individual and collective factors influencing the incomeof furniture companies in Cigasong District.Employing a quantitative approach with saturation sampling (n = 59), the study analyzes data from questionnaires administered to company owners and employees. Results reveal that working capital, labor, and raw materials all significantly impact income. T-tests and anF-test confirm individual and joint significance of these factors. These findings suggest that strategic efforts aimed at optimizing working capital, labor management, and raw material utilization can contribute to enhanced financial stability and growth for furniture companies in Cigasong District.